Music in Nature and Nursing: Musico-Philosophical Perspectives on the Ontological Dichotomies of Charles Darwin and Florence Nightingale - Dryden, Izumi (Anthropoetics, 2024)
This paper explores the musical interests of Charles Darwin and Florence Nightingale, two prominent figures of nineteenth-century England, through the lens of Generative Anthropology (GA). Darwin, in The Descent of Man (1871), classified animal voices and sounds as music, viewing them as evolutionary tools for communication and survival. Nightingale, in Notes on Nursing (1859, 1860), recognized the therapeutic roles of sound––particularly music––in patient care, emphasizing the importance of sound in the life-preserving processes of healing. Both Darwin’s and Nightingale’s musico-philosophical perspectives, when analyzed through GA, reflect deeper ontological tensions within human culture. Eric Gans’s concept of the “originary scene” (Signs of Paradox 101), where symbolic communication first emerged to prevent conflict, helps frame their views. For Darwin, music is part of the evolutionary process, a means of creating social bonds essential for species survival. Nightingale’s focus on sound in healing aligns with GA’s emphasis on the “deferral of violence” (The End of Culture 147) and the preservation of life through shared cultural practices. In both perspectives, music serves as a tool for “deferring conflict” (The End of Culture 129)—whether through evolutionary adaptation or therapeutic care—in line with GA’s understanding of how symbolic forms maintain social cohesion. Darwin and Nightingale illustrate how music, as a cultural phenomenon, bridges the creative forces of evolution and the life-sustaining efforts of nursing, embodying GA’s focus on the origins of human culture and its role in maintaining social order.